ENSIKLOPEDIA bagus untuk anak / alih bahasa Henny Susila ; penyunting, A Ary Dartoyo, Yersy Wulan, M. Surianto - Henny Susila; Ary Dartoyo; Yersy Wulan; Surianto, M (2009)
... Jilid : ilus ; 29 cm (5 eks)